Pengaruh Kualitas Pelayanan dan Kepercayaan terhadap Loyalitas Pelanggan dengan Kepuasan Pelanggan sebagai Variabel Intervening Studi Pada Pelanggan CV.AHASS Brahma Motor - Rakhman, Arif; Farida, Naili; Listyorini, Sari (Jurnal Ilmu Administrasi Bisnis, 2014)
AHASS Brahma Motor an authorized Honda motorcycle repair shop who daily serve bike repair and maintenance. With a number of rivalry then AHASS Brahma Motor must improve its services so that it can compete with other workshop. TELE SURVEY CSL (customer satisfaction measurement) held by Astra International Tbk Semarang regional offices in order to measure the implementation of Brahma Motor AHASS services to customers through a system of telephone survey respondents with a sampling of 30 people. The result is there are some attributes of service quality needs to be improved so that customers feel satisfied. The better the quality of service, the higher the level of customer satisfaction, with a good performance it will create a good confidence in the customer. If the performance of a given exceed customer expectations then the customer will not hesitate to stay loyal to the company.            This study aims to determine the effect of service quality and customer loyalty tehadap trust through customer satisfaction. The population in this study are all customers AHASS Brahma Motor in 2013 The number of samples in this study was determined using the 100 respondents to be sampled. Sampling technique in this study is purposive sampling. Measurement scale using a Likert scale. In the analysis of the data using simple linear regression and multiple regression test with SPSS 20.0 program            The results showed variable service quality affects customer satisfaction at 40.1 percent. Trust variable affects customer satisfaction at 54.5 percent. Satisfaction variables influence on customer loyalty at 42.7 percent. Variables affect service quality on customer loyalty at 24.2 percent. Trust variable effect on customer loyalty at 35.9 percent. Variable quality of service and trust affects customer satisfaction by 84 percent. Variable quality of service and trust on customer loyalty through customer satisfaction for 67.7 percent.            Based on the research results, the AHASS Brahma Motor is expected to increase the waiting room facilities, improving the cleanliness and comfort of the toilet, increasing the speed and accuracy of processing time completion of servicing the motor, provide information about obstacles and ease the damage, prioritize the needs and interests of customers, reminding service time returned to the customer, and increase empathy for the customer.